Predictors Of Antepartum Hemorrhage In Patients With Placenta Previa: Antepartum Hemorrhage In Placenta Previa - Bashir, Sadaf; Idrees, Umbreen; Chughtai, Hina Ameer; Arif, Samia; Khatoon, Nusrat; Tehseen, Saema (Pakistan Journal of Health Sciences, 2025)
Antepartum Hemorrhage (APH) is a significant complication in pregnancy that poses serious risks to both maternal and fetal health. Objective: To find the predictors of antepartum hemorrhage in patients with placenta previa among the local population of Pakistan. Methods: This cross-sectional study was conducted at PAF Hospital Mianwali from November 2023 to April 2024. A total of 208 patients were included in the analysis. Patients diagnosed with placenta previa confirmed through ultrasound examination were included in the study. Results: The mean age of the patients was 32.83 ± 4.56 years. Out of 208, there were 60 (28.8%) and nulliparous, 148 (71.2%) were multiparous. 85 (40.9%) had previous C-section and 30 (14.4%) were suffered from hypertension. 15 (7.2%) were diabetic and 180 (86.5%) were non-smokers. APH increased by 15% (Adjusted OR: 1.15, 95% CI: 1.05-1.26, p = 0.005). Furthermore, patients with a history of previous cesarean sections had over twice the odds of developing APH compared to those without this history (Adjusted OR: 2.12, 95% CI: 1.23-3.66, p = 0.007). Conclusions: This study concluded that advanced maternal age and a history of previous cesarean sections are significant predictors of antepartum hemorrhage in patients with placenta previa.